Efficacy and safety of once‐weekly exenatide after switching from twice‐daily exenatide in patients with type 2 diabetes. Issue 2 (8th October 2019) - Watanabe, Yuusuke; Saisho, Yoshifumi; Inaishi, Jun; Kou, Kinsei; Yamauchi, Akira; Kanazawa, Yasuhiko; Okubo, Yoshiaki; Tokui, Mikiya; Imai, Takatoshi; Murakami, Rie; Tsuchiya, Tami; Sasaki, Hironobu; et al.
Abstract: Aims/Introduction: To evaluate the efficacy and safety of once‐weekly (q.w.) extended‐release exenatide after switching from twice‐daily (b.i.d.) exenatide in patients with type 2 diabetes. Materials and Methods: This was an investigator‐initiated, prospective, single‐arm, multicenter study. Individuals with type 2 diabetes who had been treated with exenatide b.i.d. for at least 3 months were enrolled and switched to exenatide q.w. for 24 weeks. The primary end‐point was change in HbA1c at week 24 to test the glucose‐lowering effect of exenatide q.w. versus exenatide b.i.d. Results: A total of 58 Japanese individuals with type 2 diabetes completed the study. Glycated hemoglobin was reduced by 0.2% at week 24 (7.2 ± 1.2% vs 7.0 ± 1.2% [56 ± 13 vs 53 ± 13 mmol/mol], 95% confidence interval −0.4 to −0.03%, P  < 0.005 for non‐inferiority, P  = 0.01 for superiority). Fasting plasma glucose was reduced by 12 mg/dL at week 24 (154 ± 46 vs 142 ± 46 mg/dL, P  = 0.02). β‐Cell function assessed by homeostasis model assessment of β‐cell function and C‐peptide index was significantly improved at week 24. The incidence of self‐reported hypoglycemia was reduced, and treatment satisfaction assessed by the Diabetes Treatment Satisfaction Questionnaire and Diabetes Medication Satisfaction Questionnaire was improved at week 24, with no change in body weight. There was no serious adverse event related to the study drug. Conclusions: Switching from exenatide b.i.d. to exenatide q.w. resulted in a reduction in glycated hemoglobin, fasting plasma glucose and the incidence of hypoglycemia, and improvement in β‐cell function and treatment satisfaction in patients with type 2 diabetes. These findings will be useful for selecting optimal treatment in individuals with type 2 diabetes. Abstract : In the present study, we report the efficacy and safety of once‐weekly extended‐release exenatide after switching from twice‐daily exenatide in Japanese patients with type 2 diabetes.